Chinese Environmental Governance - Ren, Bingqiang. author. aut Link
XX, 251 p.
Keywords: In this edited volume, leading environmental policy experts from China, USA, and Europe provide a contemporary view of Chinese environmental policy, analyzing current discussions among various actors and agencies. The book covers a wide range of topics including the gap between national policy goals and their local implementation, cultural and social factors shaping political behavior, legal and political systems affecting environmental policy creation and execution, new societal forces participating in environmental policymaking and governance, and local state strategies tasked with navigating a mix of political, legal, and societal forces. Featuring in-depth, empirically-grounded analyses with interdisciplinary approaches, the book is ideal reading for scholars interested in the complex nature of balancing Chinese environmental sustainability and economic growth.